2017
DOI: 10.1016/j.lwt.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of osmotic dehydration pre-treatment on oven drying and freeze drying performance

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 27 publications
2
71
0
3
Order By: Relevance
“…The outcomes from our findings may be ascribed to the degradation of certain bioactive compounds in ginger tissues during the OD treatment that leads to a reduction in the biological activity of the dried products. Similarly, during OD treatment, the high osmotic pressure gradient results in higher water loss within the cell structure of the ginger sample, which led to changes in the biochemical properties of the sample (Prosapio & Norton, ). In all, the TFC was higher in the Ghanaian ginger compared to the Chinese ginger.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes from our findings may be ascribed to the degradation of certain bioactive compounds in ginger tissues during the OD treatment that leads to a reduction in the biological activity of the dried products. Similarly, during OD treatment, the high osmotic pressure gradient results in higher water loss within the cell structure of the ginger sample, which led to changes in the biochemical properties of the sample (Prosapio & Norton, ). In all, the TFC was higher in the Ghanaian ginger compared to the Chinese ginger.…”
Section: Resultsmentioning
confidence: 99%
“…The present investigation was carried out to study the effect of tray drying, osmotic solute, solute concentration, immersion time, temperature on the effectiveness of osmotic dehydration of Figs [4]. [5]. In osmotic dehydration the prepared samples (Fig fruit slices) were weighed approximately 200 g for every experiment and immersed in sugar (30, 40 and 50°Bx) contained in a 1000 ml steel container.…”
mentioning
confidence: 99%
“…The ability of a material to absorb and dissipate microwaves is influenced by its dielectric properties. However, the report from Prosapio and Norton about the effect of OD on FD characteristics showed that OD treatment could significantly shorten the time of FD. The difference was that OD was performed at 50 °C for 3 h with 60 °Brix fructose as the osmotic solution, and the water content of strawberry reached 187.7 g/kg.…”
Section: Resultsmentioning
confidence: 90%